THE IMPORTANCE OF ROLE-PLAY ACTIVITIES IN DEVELOPING SPEAKING SKILLS IN ENGLISH (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2026)
The article investigates the pedagogical significance of role-play as an interactive method for enhancing learners’ oral proficiency. Role-play is highlighted as a dynamic instructional strategy that provides students with realistic communication scenarios, encouraging them to practice speaking in a controlled yet authentic environment. The author emphasizes that through role-play, learners can develop fluency, build confidence, and expand their pragmatic competence by negotiating meaning, expressing opinions, and responding spontaneously in various social contexts. The study explores different types of role-play activities, including simulations, dialogues, and situational enactments, showing how each activity fosters active student engagement, collaborative learning, and experiential understanding of language use. It also underscores the importance of teacher guidance in structuring role-play tasks, giving clear instructions, and providing constructive feedback to maximize learning outcomes.